Is the Current Reality Conducive to the Implementation of Sustainable Development? - Sztumski, Wiesław (Problemy Ekorozwoju, 2023)
The idea of sustainable development did not appear in the eighteenth century for ecological reasons to save the environment or humanitarian reasons to save humanity, but for economic reasons to improve the management of forests and fossil resources. Its creator was Hans Carl v. Carlowitz (1645-1714), a Saxon tax accountant and mining administrator. The idea has always served an economic purpose – constant economic growth as well as increase of productivity and profit. Therefore, it worked best in the sphere of management. Over time, it turned out that one could achieve better economic effects. when one combines economic goals with those that people have always strived for – to create a better world, life and interpersonal relations. This requires care for the good condition of the natural and social environment. Consequently, the idea of sustainable development was coupled with the goals of ecology and sozology. Unfortunately, for various reasons, the modern world is less and less conducive to achieving these goals. Therefore, one can increasingly difficult implement the postulates of sustainable development, even in the sphere of economy. It has become clear that sustainable development is not a panacea for all the ills of the world. The idea of this unrealizable development turned into a myth and a tool to manipulate people’s feelings and dreams of a better life. With their help, one mobilizes people to higher and higher productivity, which generates an increase in the enrichment of the financial elite and to the accompanying to it deepening of social inequalities, which are the source of all the evil.